King of the wind - Henry, Marguerite, 1902-1997.; Dennis, Wesley (New York : Aladdin Paperbacks, 1991)
Sham and the stable boy Agba travel from Morocco to France to England where, at last, Sham's majesty is recognized and he becomes the "Godolphin Arabian," ancestor of the most superior Thoroughbred horses.
Wilson's Children, June 2001
Elem. School Library Collection, June 2000
Book Links (A.L.A.), July 1995
Child Study Children's Book Committee, January 2007
L.A. Recommended Foreign Language, February 1999
5.5
Keywords: Horses -- Fiction; Horses -- Fiction